2003
DOI: 10.1046/j.1365-2958.2003.03756.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness effects of DHFR‐TS mutations associated with pyrimethamine resistance in apicomplexan parasites

Abstract: SummaryPyrimethamine resistance in the malaria parasite Plasmodium falciparum is characterized by specific point mutations in the dihydrofolate reductase (DHFR) domain of the bifunctional dihydrofolate reductasethymidylate synthase (DHFR-TS) gene. We have previously explored the effect of these mutations by engineering homologous alleles of Toxoplasma gondii DHFR-TS, which can readily be expressed as recombinant protein for enzymatic studies, or as allelic replacements in transgenic parasites. In order to dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Our initial characterization of the TgIF2α-S71A parasites indicated that the mutants took longer to lyse monolayers of host cells compared with WT. To directly assess whether the mutant parasites had decreased fitness relative to WT, we performed "headto-head" competition assays (17) in which an equal number of WT and TgIF2α-S71A parasites were inoculated into the same culture flask of host cells, human foreskin fibroblasts (HFF) ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial characterization of the TgIF2α-S71A parasites indicated that the mutants took longer to lyse monolayers of host cells compared with WT. To directly assess whether the mutant parasites had decreased fitness relative to WT, we performed "headto-head" competition assays (17) in which an equal number of WT and TgIF2α-S71A parasites were inoculated into the same culture flask of host cells, human foreskin fibroblasts (HFF) ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The comparative fitness assay was based on a protocol outlined in ref. 17. After filter purification, 5 × 10 5 parental ΔKu80 (WT) and TgIF2α-S71A mutant parasites were mixed in 10 mL DMEM + 1% FBS and added to a T-25 cm 2 flask containing a monolayer of HFF host cells.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, however, we have found that sensitive competition assays enable the detection of subtle fitness defects in other mutants (22). As shown in Fig.…”
Section: Expression Of L Donovani Aprt In T Gondii-to Furthermentioning
confidence: 96%
“…Fitness Assays-Competition assays between the parental wild-type and ⌬HXGPRT and ⌬AK parasites were performed as described (22). For detection of viable wild-type or knockout parasites at various timepoints, plaque assays were performed in 6-well plates in the presence of suitable selective drugs (15).…”
Section: Expression Of Leishmania Donovani Aprt In T Gondii-mentioning
confidence: 99%
“…It has been shown in a wide variety of organisms that acquisition of drug resistance can incur a biological cost (Bjorkman et al ., 2000;Nagaev et al ., 2001;Fohl and Roos, 2003;Lu et al ., 2004;Mariam et al ., 2004). Genetic mutations that alter the structure or function of key proteins in order to evade the actions of deleterious compounds may also compromise the normal function of those proteins.…”
Section: Introductionmentioning
confidence: 99%